Establishing Cool‐Season Grasses on a Degraded Arid Rangeland of the Colorado Plateau. Issue 1 (22nd May 2013) - Bernstein, Eli J.; Albano, Christine M.; Sisk, Thomas D.; Crews, Timothy E.; Rosenstock, Steve
Abstract Reestablishing cool‐season (C3) grass communities on low elevation rangelands of the Colorado Plateau is notoriously difficult, raising questions about the viability of restoring native species and continuing to actively graze these landscapes. We conducted a seeding experiment on an arid (15.4 cm rain/year), historically heavily‐grazed rangeland in Northern Arizona to test the effects of seeding technique and simulated seasonal climate scenarios on germination and recruitment of four species of native, cool‐season bunchgrasses: Achnatherum hymenoides, Hesperostipa comata, Poa secunda, and Elymus elymoides. Initial results indicated that C3 grasses germinated significantly more in drill‐seeded treatments under simulated high precipitation years than in other treatment types. Five years post‐treatment, P. secunda and E. elymoides were not observed but simulated drill‐seeded treatments, had significantly higher densities of A. hymenoides and H. comata recruits relative to most other treatment types. Simulated drill seeding also increased soil disturbance which increased the establishment of the invasive weed Salsola tragus in year 1, but not thereafter. Although it appears critical to coordinate effective seeding techniques with high winter–spring precipitation, predicting such events may not be possible at some sites, suggesting that seeding low elevation, arid rangelands of the Colorado Plateau may not always be realistic under a future climate that is drier and less predictable.